Akuntansi Lingkungan dan Kinerja Keuangan Perusahaan dalam Ekonomi Syariah - Nur Wahyu Ningsih; Nurlaili Nurlaili; Ahmad Zuliansyah (Jurnal Ilmiah Ekonomi Islam, 2022)
Many companies in Indonesia use natural resources, both ocean and land products, as raw materials for the company's production. Currently in Indonesia, disclosure of environmental accounting has not been specifically regulated in accounting standards, meaning that the reporting of environmental information in the company's annual report is still voluntary. If there are companies that have not reported environmental costs, there is no specific policy from the government, even though company waste can damage the surrounding environment if it is not managed properly.The purpose of this research is to know the environmental costs and financial performance in the perspective of Islamic economics. Quantitative methods are used in this study and use Smart PLS 3.0. The results showed that there was an effect of environmental costs on the financial performance of ROA, ROE, and NPM. The universe that has been created by Allah SWT must be preserved for the sake of safety on earth. Humans as caliphs on earth are given the responsibility to preserve nature. PT X has carried out its responsibility towards the environment in accordance with the Sharia Enterprise Theory, namely Allah SWT as the highest stakeholder.